PARAFAC Analysis for Temperature-Dependent NMR Spectra of Poly(Lactic Acid) Nanocomposite - Shinzawa, Hideyuki; Nishida, Masakazu; Tanaka, Toshiyuki; Suzuki, Kenzi; Kanematsu, Wataru (IntechOpen, 2012)
None